2016
DOI: 10.1002/app.43128
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the effects of perlite additive on some comfort and acoustical properties of polyester fabrics

Abstract: Natural perlite material was added for the first time into a polyester filament yarn structure. The water absorption and heat and sound insulation properties of the fabrics produced from textured and twisted polyester yarns containing 1.25% perlite additive were tested, and the results were compared with those obtained on the fabrics produced from reference polyester yarns. Although there are differences between the mechanical properties of the polyester yarns, the yarns including perlite remained within comme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 27 publications
(47 reference statements)
0
7
0
Order By: Relevance
“…When the results were examined according to the contact and radiant measurement principles, it was seen that they were compatible with each other, and perlite coating contributed to thermal insulation property like other studies in the literature. 25,37,38 Additionally, to evaluate the influence of particle size and concentration of filler on thermal results of coated samples, ANOVA and SNK tests were conducted. The results given in Table 9 showed that perlite concentration was an influential factor for all thermal outputs.…”
Section: Thermal Measurement Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When the results were examined according to the contact and radiant measurement principles, it was seen that they were compatible with each other, and perlite coating contributed to thermal insulation property like other studies in the literature. 25,37,38 Additionally, to evaluate the influence of particle size and concentration of filler on thermal results of coated samples, ANOVA and SNK tests were conducted. The results given in Table 9 showed that perlite concentration was an influential factor for all thermal outputs.…”
Section: Thermal Measurement Resultsmentioning
confidence: 99%
“…17 Karaca et al investigated the water absorption, heat and sound insulation properties of the woven fabrics produced from polyester yarns containing perlite additive. 25 Tiber investigated some properties of cotton fabrics coated on both sides with raw and expanded perlite, such as thermal conductivity, antibacterial properties, and sound absorption. 26 Davraz et al investigated the production of monolithic thermal insulation material using coarse and fine raw perlite.…”
Section: Introductionmentioning
confidence: 99%
“…The production details of the processes prior to yarn production (properties of the raw perlite material, grinding process, perlite surface modification process, perlite size distribution after grinding, and other production details) were presented in the former paper. 19 Plain woven fabrics were produced using perlite-containing and reference (regular) polyester yarns in both the warp and weft directions. Thus, two different polyester fabrics, one containing yarns with the perlite additive and one containing the regular (reference) fibers, were produced.…”
Section: Methodsmentioning
confidence: 99%
“…The results were presented in an earlier paper. 19 Some comfort, tensile, thermal resistance, and acoustical properties of these fabrics besides their water vapor resistance were reported. 19,20 However, the dyeing and fastness properties of fabrics produced from polyester fibers having perlite additive have not been studied yet.…”
Section: Dyeing and Some Fastness Properties Of Novel Perlite-contain...mentioning
confidence: 99%
“…Applications of polyethylene prepared with the addition of PT have been reported previously [26,27]. Recently, Karaca et al [28] showed that PT enhanced the thermal stability and sound absorption coefficients of polyesters. However, there have until now been no reports in the literature regarding the application of VMT and PT fillers in ethylene-propylene rubber (EPM) elastomer to improve its fire retardancy.In this work, natural PT and VMT materials were added for the first time to EPM rubber at different concentrations and studied for their effects on its mechanical and flame-resistant properties.…”
mentioning
confidence: 99%